The effect of training in raising the efficiency of employee performance - An exploratory study on governmental and private organizations in Jeddah- - Al-Zahrani, Salih Saeed (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at shed light on the topic of training and its importance in relation to human resources, to identify the methods of success and failure of training programs, to highlight the role of training in improving the performance of human resources and to know the principles on which training is based. The study assumed that there is no significant relationship between training and productivity of workers at a level of statistical significance (α
Keywords: Impact; training; Employee performance efficiency